Case Report: Long-term suppression of relapses by dimethyl fumarate in a relapsing pediatric patient with myelin oligodendrocyte glycoprotein antibody–associated disease manifesting as acute disseminated encephalomyelitis, unilateral optic neuritis, and seizure episodes - Tahara, Masayuki; Awaya, Tomonari; Saito, Keisuke; Sawada, Hideyuki (Frontiers in Immunology, 2025)
BackgroundMyelin oligodendrocyte glycoprotein (MOG) antibody-associated diseases (MOGAD), which has been recognized as a distinct entity in patients with neuromyelitis optica spectrum disorders, often presents with acute disseminated encephalomyelitis (ADEM) symptoms in pediatric patients. Appropriate treatment based on accurate diagnosis is challenging in relapsing pediatric patients with MOGAD.Case PresentationAn 11-year-old girl experienced relapses four times, exhibiting brainstem symptoms, an ADEM episode, seizures, and optic neuritis (ON). She was initially diagnosed with multiple sclerosis and received interferon beta-1a therapy with a mild effect on relapse suppression. She was then transferred from the pediatric department to the department of neurology of our hospital. Two months before her referral visit, she experienced left optic neuritis, and her annualized relapse rate reached 0.6. She desired to switch from the injectable treatment to oral dimethyl fumarate (DMF) administration. At that time, she was found to be seropositive for MOG antibody, but after that had no relapses for more than five years. Moreover, her seropositivity for serum MOG-antibody turned out to be seronegative.ConclusionsDMF showed long-term effects on suppressing relapses in a pediatric patient with MOGAD, revealing its potential as a treatment option for such patients.